TEXT BETRAYAL VERSUS CULTURAL LOYALTY: EMPLOYED STRATEGIES IN TRANSLATING ARABIC POETIC TEXT INTO ENGLISH - M Abd Al-Salam, Ahmad; Mabrouk, Aya Awad Shehata (International Journal For Research In Educational Studies, 2023)
Translating Arabic poetry into English or any European or (anti-Semitic) language constitutes an essential burden on the translator due to their common origins that are similar in terms of rhetorical uses (e.g., synecdoche, metaphor, simile, euphemism, and the most important of all, similarity in grammatical, morphological and derivational linguistic rules). In the case of rendering Arabic poetry into English, the gap is vast and this requires a double effort, wider knowledge, and a high-level culture awareness on part of the translator. More importantly, the translator has to be equipped with an abundant knowledge of the means of influence that fall within the circle of rhetoric methods that may be unique to both Arabic and English languages. That is what we called Text Betrayal Versus Cultural Loyalty.